PENGARUH PROFITABILITAS, SOLVABILITAS, DAN AKTIVITAS TERHADAP NILAI PERUSAHAAN - Adian Sahyu; Novera Kristianti Maharani (Komitmen: Jurnal Ilmiah Manajemen, 2023)
The purpose of this study is to determine whether profitability, solvency, and activity can affect company value. The independent variables used in this study are profitability proxied by Return On Equity, solvency proxied by Debt to Equity Ratio, and activity proxied by Total Asset Turn Over. The population used in this study were 47 companies, which are service industry companies. The wholesale trade sub-sector of production goods and consumer goods listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period was 47 companies, with samples taken from 13 companies. so that the total sample data is 65, and the sample selection procedure is carried out by applying the purposive sampling method. The analysis in this study uses multiple regression with the SPSS version 26 application. The results of this study indicate that profitability have a positive effect on company value, solvency and activity have no effect on company value.